(untitled) (Journal of Computational Mathematics, 1990)
In this paper we present a posteriori error estimator in a suitable norm of mixed finite element solution for two-dimensional stationary Stokes problem. The estimator is optimal in the sense that, up to multiplicative constant, the upper and lower bounds of the error are the same. The constants are independent of the mesh and the true solution of the problem.